Night train : a novel - Amis, Martin (New York : Harmony Books, 1997)
An investigation into the suicide of Jennifer Rockwell, a woman with everything going for her--health, looks, man-- plus a job as an astrophysicist. Question is, can a person shoot herself in the head three times? As she investigates the victim's background, policewoman Mike Hoolihan thinks she can. By the author of The Information.
"Originally published in Great Britain by Jonathan Cape Ltd. in 1997"--T.p. verso.
Keywords: Policewomen -- Fiction; Suicide victims -- Fiction; Psychological fiction